Oxygen storage material and method for producing same

By adding tin, scandium, or magnesium to ceria-zirconia composite oxides and applying specific processing techniques, the material achieves superior oxygen storage capacity and efficiency, addressing the limitations of conventional materials in high-temperature environments.

JP7601824B2Active Publication Date: 2024-12-17KK TOYOTA CHUO KENKYUSHO +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022050279
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-25
Publication Date
2024-12-17
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

Conventional oxygen storage materials do not adequately meet the increasing demand for high oxygen storage capacity and efficiency, especially at low temperatures and after exposure to high temperatures for extended periods, necessitating improved ceria-zirconia composite oxides.

Method used

Incorporating tin, scandium, or magnesium as additional metal elements into ceria-zirconia composite oxides, with specific content ratios and processing conditions, including pressure molding and high-temperature reduction treatments, to achieve a pyrochlore type ceria-zirconia composite oxide with enhanced oxygen storage capacity and stability.

Benefits of technology

The resulting oxygen storage material exhibits excellent oxygen storage capacity at low temperatures and maintains high efficiency even after exposure to high temperatures, making it suitable for use in exhaust gas purification catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601824000002
    Figure 0007601824000002
  • Figure 0007601824000003
    Figure 0007601824000003
  • Figure 0007601824000004
    Figure 0007601824000004
Patent Text Reader

Abstract

To provide an oxygen storage material which can show an excellent oxygen storage capacity (OSC) at a low temperature of about 250°C not only in an initial stage in use but also after exposed to exhaust gas at a high temperature of about 1100°C for a long time, exhibiting high utilization efficiency.SOLUTION: An oxygen storage material includes: pyrochlore ceria-zirconia complex oxide; and at least one type of added metal element M added to the ceria-zirconia complex oxide, selected from the group consisting of Sn, Sc, and Mg. A content percentage (M / (Ce+Zr)×100) of the added metal element M to a total amount of Ce and Zr is 0.4 to 5.5 at%. A molar fraction (X=Zr / (Ce+Zr)×100) of Zr to a total molar number of Ce and Zr satisfies X=44.5 to 49.9%. The oxygen storage material has a lattice constant determined from an X-ray diffraction pattern obtained by X-ray diffraction measurement with CuKα before heated at 1100°C in the atmosphere and after heated at 1100°C in the atmosphere for 5 hours, the lattice constant satisfying a condition represented as the following formula (1): lattice constant≤-9.69×10-3X+11.009 (1). The oxygen storage material exhibits an intensity ratio (I (14 / 29) value) of a diffraction line at about 2θ=14.5° to a diffraction line at about 2θ=29° satisfying a condition represented as the following formula (2): I (14 / 29) value≤5.15×10-3X-0.196 (2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxygen storage material containing a pyrochlore-type ceria-zirconia composite oxide and a method for producing the same. [Background technology]

[0002] Three-way catalysts are known as exhaust gas purification catalysts that can oxidize carbon monoxide (CO) and hydrocarbons (HC) in exhaust gas emitted from internal combustion engines such as automobile engines, while simultaneously reducing nitrogen oxides (NOx).

[0003] In purifying exhaust gas using an exhaust gas purification catalyst, in order to absorb fluctuations in the oxygen concentration in the exhaust gas and increase the exhaust gas purification capacity, it is known to use a material with oxygen storage capacity (Oxygen Storage Capacity (OSC)) that can store oxygen when the oxygen concentration in the exhaust gas is high and release oxygen when the oxygen concentration in the exhaust gas is low as a support or co-catalyst for the exhaust gas purification catalyst.

[0004] As an oxygen storage material having such an OSC, ceria has conventionally been used suitably. In recent years, various types of composite oxides containing ceria have been researched, and various ceria-zirconia composite oxides obtained by the so-called coprecipitation method, reverse coprecipitation method, hydrothermal synthesis method, melting method, solid phase method, etc. have been developed.

[0005] For example, JP 2015-182931 A (Patent Document 1) discloses a method for producing a ceria-zirconia composite oxide that contains cerium, zirconium, and other transition metal elements such as iron, manganese, cobalt, nickel, and copper, and has a pyrochlore phase as a crystal structure, by a so-called melting method.

[0006] Furthermore, JP 2015-080736 A (Patent Document 2) discloses a method for producing an oxygen absorbing / releasing material comprising ceria-zirconia composite oxide having a pyrochlore phase, a κ phase or a combination thereof and containing no precious metal, with the iron at least partially substituting for cerium sites and / or zirconium sites in the ceria-zirconia composite oxide, by a so-called coprecipitation method and high-temperature treatment in a reducing atmosphere (coprecipitation method-high-temperature reduction treatment).

[0007] Furthermore, JP 2019-131455 A (Patent Document 3) discloses a method for producing an oxygen absorbing / releasing material made of a ceria-zirconia-iron oxide-based composite oxide containing cerium, zirconium, and iron, in which at least a portion of the iron is dissolved in the composite oxide of the cerium and the zirconium, and the ceria-zirconia-iron oxide-based composite oxide has a cation-ordered structure, by a so-called solution combustion synthesis method.

[0008] However, in recent years, the required characteristics of exhaust gas purification catalysts have been increasing, and there is a demand for oxygen storage materials that can exhibit excellent oxygen storage capacity (OSC) at a low temperature of about 250°C and have high utilization efficiency, not only at the initial stage of use but also after long-term exposure to high-temperature exhaust gases of about 1100°C. Conventional oxygen storage materials such as those described in Patent Documents 1 to 3 have not necessarily been sufficient. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2015-182931 A [Patent Document 2] JP 2015-080736 A [Patent Document 3] JP 2019-131455 A Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made in consideration of the problems associated with the above-mentioned conventional techniques, and aims to provide an oxygen storage material that exhibits excellent oxygen storage capacity (OSC) at a low temperature of about 250°C, not only in the initial stage of use but also after prolonged exposure to high-temperature exhaust gases at about 1100°C, and has high utilization efficiency, and a method for producing the same. [Means for solving the problem]

[0011] As a result of intensive research to achieve the above object, the present inventors have found that by selecting tin, scandium or magnesium (hereinafter, these will be referred to as "additive metal elements") as an element to be added to a ceria-zirconia composite oxide, and adjusting the content ratio of cerium, zirconium and the added metal element within a predetermined range, and then pressure-molding the added metal element-containing ceria-zirconia solid solution powder at a predetermined pressure, followed by reduction treatment under predetermined high-temperature conditions and further oxidation treatment, the added metal element-containing ceria-zirconia composite oxide in which the added metal element is sufficiently dissolved in the ceria-zirconia composite oxide can be obtained both before and after exposure to high-temperature exhaust gas of about 1100°C for a long period of time, and that this added metal element-containing ceria-zirconia composite oxide can exhibit excellent oxygen storage capacity (OSC) at a low temperature of about 250°C not only in the initial stage of use but also after exposure to high-temperature exhaust gas of about 1100°C for a long period of time, and has high utilization efficiency as an oxygen storage material, thereby completing the present invention.

[0012] That is, the oxygen storage material of the present invention is a pyrochlore type ceria-zirconia composite oxide and Tin and Scandium and at least one additional metal element selected from the group consisting of: The content ratio (M / (Ce+Zr)×100) of the added metal element (M) relative to the total amount of cerium (Ce) and zirconium (Zr) is 0.4 to 5.5 at %, The mole fraction of zirconium relative to the total mole number of cerium (Ce) and zirconium (Zr) (X = Zr / (Ce + Zr) × 100) is X = 44.5 to 49.9%, The lattice constant calculated from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα before and after heating at 1100°C in air for 5 hours is expressed by the following formula (1): Lattice constant ≦-9.69×10-3X+11.009 (1) (In the above formula, X represents the mole fraction of zirconium.) The condition expressed by The intensity ratio [I(14 / 29) value] of the diffraction line near 2θ=14.5° and the diffraction line near 2θ=29° obtained from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα before and after heating at 1100°C in air is expressed by the following formula (2): I(14 / 29) value ≦ 5.15 × 10-3 × -0.196 (2) (In the above formula, X represents the mole fraction of zirconium.) The present invention is characterized in that it satisfies the condition expressed by the following formula (1).

[0013] In the oxygen storage material of the present invention, the zirconium molar fraction X is preferably 47.0 to 49.9%.

[0014] Further, the present invention provides a method for producing an oxygen storage material comprising a pyrochlore-type ceria-zirconia composite oxide and at least one additive metal element selected from the group consisting of tin, scandium, and magnesium added to the ceria-zirconia composite oxide, the method comprising the steps of: preparing a ceria-zirconia solid solution powder containing the additive metal element (M), in which the content ratio (M / (Ce+Zr)×100) of the additive metal element (M) relative to the total amount of cerium (Ce) and zirconium (Zr) is 0.4-5.5 at% and the molar fraction (Zr / (Ce+Zr)×100) of zirconium relative to the total number of moles of cerium (Ce) and zirconium (Zr) is 44.5-49.9%; a step of compressing the ceria-zirconia solid solution powder containing the additive metal element at a pressure of 30 to 350 MPa, reducing the powder at a temperature of 1400 to 2000°C, and then oxidizing the powder to obtain an oxygen storage material containing the pyrochlore-type ceria-zirconia composite oxide according to claim 1 or 2 and the additive metal element added to the ceria-zirconia composite oxide; The method is characterized by comprising:

[0015] In the method for producing an oxygen storage material of the present invention, the molar fraction of zirconium in the additive metal element-containing ceria-zirconia solid solution powder (Zr / (Ce+Zr)×100) is preferably 47.0 to 49.9%.

[0016] In the present invention, the reason why the pyrochlore-type ceria-zirconia composite oxide containing the additive metal element, which satisfies the condition represented by the formula (1), can be judged to be one in which the additive metal element is sufficiently dissolved, will be explained below. That is, in a pyrochlore-type ceria-zirconia composite oxide not containing the additive metal element, the lattice constant shows a negative correlation with the mole fraction X of zirconium. This is because, in a pyrochlore-type ceria-zirconia composite oxide, as the mole fraction X of zirconium increases, that is, as the ionic radius of Ce increases, the lattice constant of the pyrochlore-type ceria-zirconia composite oxide increases. 4+ (Ionic radius: 0.97 Å (8 coordinates)) compared to Zr 4+ It is believed that as the proportion of cations (ionic radius: 0.84 Å (8 coordination)) increases, the average ionic radius of all cations in the crystal lattice becomes smaller, causing the lattice to shrink.

[0017] The pyrochlore-type ceria-zirconia composite oxide not containing the additive metal element has an ionic radius of Zr 4+ Smaller than Sn 4+ When zirconium (ion radius: 0.81 Å) is dissolved in a solid solution, the average ionic radius of all cations in the crystal lattice becomes smaller, and the lattice contracts further compared to when the added metal element is not included, even if the mole fraction X of zirconium is the same, and the lattice constant becomes smaller.

[0018] On the other hand, a pyrochlore-type ceria-zirconia composite oxide not containing the above-mentioned additive metal element is added with Zr 4+ When a metal ion with a larger ionic radius than Zr is dissolved in a solid solution, the average ionic radius of all cations in the crystal lattice becomes larger, causing the lattice to expand. 4+ When a metal ion with a lower valence than Zr is dissolved in the solid solution, oxygen vacancies are generated due to charge compensation, causing the lattice to shrink. 4+ When a metal ion having a larger ionic radius and a smaller valence than Zr is dissolved in the solid solution, the lattice expansion effect due to the increase in the ionic radius competes with the lattice contraction effect due to the generation of oxygen defects. 4+ Sc has a larger ionic radius and a smaller ionic valence than 3+ (ionic radius 0.87 Å) and Mg 2+ When an oxide ion (ion radius 0.89 Å) is dissolved, the ionic radius of the oxide ion (1.38 Å) is sufficiently larger than the ionic radius of the Zr site. Therefore, the effect on the lattice is greater due to the generation of oxygen defects than the increase in the ionic radius due to the dissolved metal ion, and the lattice constant tends to decrease as the dissolution of the metal ion progresses.

[0019] Therefore, in the present invention, the compound represented by the following formula (1a): Lattice constant (Y1) = -9.69 x 10 -3 X+11.009 (1a) If the straight line represented by represents the boundary between a state in which the added metal element is sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide and a state in which the added metal element is not sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide, when the measured lattice constant is equal to or less than the lattice constant (Y1), that is, when the condition represented by the formula (1) is satisfied, it can be determined that the added metal element is sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide, and when the measured lattice constant is greater than the lattice constant (Y1), that is, when the condition represented by the formula (1) is not satisfied, it can be determined that the added metal element is not sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide. The lattice constant can be determined by fitting the X-ray diffraction pattern obtained by X-ray diffraction measurement using a free analysis software (for example, Rietveld analysis software "Jana2006") by the least squares method to refine the lattice constant. The X-ray diffraction measurement is performed using an X-ray diffraction device (e.g., RINT-Ultima manufactured by Rigaku Corporation) with CuKα radiation as the X-ray source under conditions of a tube voltage of 40 KV, a tube current of 40 mA, and a scanning speed of 2θ=10° / min.

[0020] In addition, in the present invention, the reason why the pyrochlore-type ceria-zirconia composite oxide containing the additive metal element, which satisfies the condition represented by the formula (2), can be judged to be one in which the additive metal element is sufficiently dissolved in solid solution, will be explained below. That is, in a pyrochlore-type ceria-zirconia composite oxide not containing the additive metal element, the I(14 / 29) value shows a positive correlation with the zirconium mole fraction X. This is because the I(14 / 29) value of the pyrochlore-type ceria-zirconia composite oxide is determined by the difference in ionic radius between the Ce site and the Zr site in the crystal lattice, and the smaller this difference is, the smaller the I(14 / 29) value is. Therefore, as the zirconium mole fraction X decreases, i.e., Zr 4+ Ce 4+ When the ratio of Zr increases, some of the Zr sites with a small ionic radius are occupied by Ce. 4+ This is believed to be because the difference in ionic radius between the Ce site and the Zr site becomes smaller.

[0021] The pyrochlore-type ceria-zirconia composite oxide not containing the additive metal element was mixed with Sn. 4+ When it is dissolved, Sn 4+ The ionic radius of Zr 4+ Since the ionic radius of the Zr site is smaller than that of the Ce site, the difference in ionic radius between the Ce site and the Zr site increases, and the I(14 / 29) value increases. 4+ When the amount of solid solution is small, the change in the ionic radius difference between the Ce site and the Zr site is small, and therefore it is considered that the I(14 / 29) value hardly changes at all.

[0022] On the other hand, a pyrochlore-type ceria-zirconia composite oxide not containing the above-mentioned additive metal element is added with Zr 4+ Sc has a larger ionic radius than 3+ or Mg 2+ When these are dissolved, the difference in ionic radius between the Ce site and the Zr site becomes smaller, and the I(14 / 29) value becomes smaller.

[0023] Therefore, in the present invention, the following formula (2a): I(14 / 29) value(Y2)=5.15×10 -3 X-0.196 (2a) If the line represented by the formula (2) represents the boundary between the state where the added metal element is sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide and the state where the added metal element is not sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide, when the measured I(14 / 29) value is equal to or less than the I(14 / 29) value (Y2), that is, when the condition represented by the formula (2) is satisfied, it can be determined that the added metal element is sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide, and when the measured I(14 / 29) value exceeds the lattice constant (Y2), that is, when the condition represented by the formula (2) is not satisfied, it can be determined that the added metal element is not sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide. The I(14 / 29) value can be calculated from the peak intensity I(14) of the diffraction line at 2θ=14.5° and the peak intensity I(29) of the diffraction line at 2θ=29° in the X-ray diffraction pattern obtained by X-ray diffraction measurement. The X-ray diffraction measurement method employs an X-ray diffraction device (e.g., "RINT-Ultima" manufactured by Rigaku Corporation) using CuKα radiation as the X-ray source under the conditions of tube voltage 40 KV, tube current 40 mA, and scan speed 2θ=10° / min. The intensity (peak intensity) of the diffraction radiation is calculated after removing Kα2 and background using commercially available analysis software (e.g., "JADE" manufactured by Materials Data Corporation).

[0024] Furthermore, the oxygen storage material of the present invention can exhibit excellent oxygen storage capacity (OSC) at a low temperature of about 250°C not only in the initial stage of use but also after long-term exposure to high-temperature exhaust gases at about 1100°C, and the reason why the utilization efficiency is high is not necessarily clear, but the inventors speculate as follows. That is, the superlattice structure of CeO2-ZrO2 in the ceria-zirconia composite oxide containing the additive metal element that constitutes the oxygen storage material of the present invention undergoes a phase change between the pyrochlore phase (Ce2Zr2O7) and the κ phase (Ce2Zr2O8) depending on the oxygen partial pressure in the gas phase, and exhibits oxygen storage capacity (OSC). Sn 4+ , Sc 3+ and Mg 2+ The ionic radius of Zr 4+Since the ionic radius of the added metal ions is close to that of the Ce site, it is considered that the added metal ions selectively substitute for the Zr site in the added metal element-containing ceria-zirconia composite oxide according to the present invention. When the Zr site is substituted with an Sn ion, the ionic radius difference between the Ce site and the Zr site is enlarged, and the superlattice structure is more stabilized. When the Zr site is substituted with an Sc ion or an Mg ion, the superlattice structure in a state including oxygen defects generated by charge compensation is more stabilized. Therefore, it is presumed that the oxygen storage material of the present invention can exhibit excellent oxygen storage capacity (OSC) at a low temperature of about 250°C even after being exposed to high-temperature exhaust gas of about 1100°C for a long period of time, and the utilization efficiency is increased. Effect of the Invention

[0025] According to the present invention, it is possible to obtain an oxygen storage material with high utilization efficiency, which exhibits excellent oxygen storage capacity (OSC) at a low temperature of about 250°C not only at the initial stage of use but also after long-term exposure to high-temperature exhaust gas at about 1100°C. [Brief description of the drawings]

[0026] [Figure 1] 1 is a graph showing the results of plotting the lattice constants of the composite oxide powders obtained in Examples 1 to 6 and Comparative Examples 1 to 4 before and after a high-temperature durability test against the zirconium mole fraction X. [Diagram 2] 1 is a graph showing the results of plotting the I(14 / 29) values ​​of the composite oxide powders obtained in Examples 1 to 6 and Comparative Examples 1 to 4 against the zirconium mole fraction X before and after a high-temperature durability test. [Diagram 3] 1 is a graph showing the results of plotting the OSC material utilization rate of catalyst powder against the zirconium mole fraction X for the composite oxide powders obtained in Examples 1 to 6 and Comparative Examples 1 to 4 after a high-temperature durability test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The present invention will be described in detail below based on preferred embodiments thereof.

[0028] First, the oxygen storage material of the present invention will be described. The oxygen storage material of the present invention is an oxygen storage material containing a pyrochlore-type ceria-zirconia composite oxide and at least one additive metal element selected from the group consisting of tin, scandium, and magnesium added to the ceria-zirconia composite oxide, The content ratio (M / (Ce+Zr)×100) of the added metal element (M) relative to the total amount of cerium (Ce) and zirconium (Zr) is 0.4 to 5.5 at %, The mole fraction of zirconium relative to the total mole number of cerium (Ce) and zirconium (Zr) (X = Zr / (Ce + Zr) × 100) is X = 44.5 to 49.9%, The lattice constant calculated from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα before and after heating at 1100°C in air for 5 hours is expressed by the following formula (1): Lattice constant ≦-9.69×10 -3 X+11.009 (1) (In the above formula, X represents the mole fraction of zirconium.) The condition expressed by The intensity ratio [I(14 / 29) value] of the diffraction line near 2θ=14.5° and the diffraction line near 2θ=29° obtained from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα before and after heating at 1100°C in air is expressed by the following formula (2): I(14 / 29) value ≦ 5.15 × 10 -3 X-0.196 (2) (In the above formula, X represents the mole fraction of zirconium.) It satisfies the condition expressed by:

[0029] The oxygen storage material of the present invention is made of a ceria-zirconia composite oxide having a superlattice structure in which Ce and Zr are regularly arranged (hereinafter referred to as "pyrochlore-type ceria-zirconia composite oxide"). The oxygen storage material made of such a pyrochlore-type ceria-zirconia composite oxide has a higher oxygen diffusion rate in the bulk than a ceria-zirconia composite oxide having a fluorite structure, and therefore has excellent oxygen storage capacity (OSC). Note that by recognizing the presence of a peak (peak appearing at 2θ=14.0° to 16.0°) derived from the superlattice structure in an X-ray diffraction measurement using CuKα rays, it can be confirmed that the ceria-zirconia composite oxide is a pyrochlore type having a superlattice structure.

[0030] The oxygen storage material of the present invention further contains at least one additive metal element selected from the group consisting of tin (Sn), scandium (Sc) and magnesium (Mg) added to such pyrochlore-type ceria-zirconia composite oxide. By dissolving these additive metal elements, the oxygen storage capacity (OSC) at low temperatures and the utilization efficiency as an oxygen storage material are improved. Among these additive metal elements, tin is preferred from the viewpoint of improving the oxygen storage capacity (OSC) at low temperatures and suppressing the decrease in heat resistance, and scandium and magnesium are preferred from the viewpoint of improving the low-temperature operation of oxygen by generating oxygen defects while ensuring heat resistance.

[0031] The content of such an additive metal element, expressed as the content ratio (M / (Ce+Zr)×100) of the additive metal element (M) to the total amount of cerium (Ce) and zirconium (Zr), must be 0.4-5.5 at%, and is more preferably 1-3 at%. If the content of the additive metal element is less than the lower limit, the effect of improving the oxygen storage capacity (OSC) at low temperatures and the effect of improving the utilization efficiency as an oxygen storage material due to the solid solution of the additive metal element cannot be sufficiently obtained. On the other hand, if the content of the additive metal element exceeds the upper limit, the additive metal element does not sufficiently dissolve, and the effect of improving the oxygen storage capacity (OSC) at low temperatures and the effect of improving the utilization efficiency as an oxygen storage material cannot be sufficiently obtained.

[0032] Even if the additive metal element is added to a ceria-zirconia composite oxide, it is difficult to sufficiently dissolve the additive metal element in the ceria-zirconia composite oxide by methods such as so-called solid-phase synthesis and hydrothermal synthesis, and therefore the addition of the additive metal element does not contribute to improving the oxygen storage capacity (OSC) at low temperatures or improving the utilization efficiency as an oxygen storage material. In contrast, in the present invention, by the production method of the present invention described below, it is possible to obtain the additive metal element-containing ceria-zirconia composite oxide in which the additive metal element is sufficiently dissolved, which was not possible to obtain in the past, and it is possible to achieve an improvement in the oxygen storage capacity (OSC) at low temperatures and an improvement in the utilization efficiency as an oxygen storage material.

[0033] In the oxygen storage material of the present invention, the molar fraction of zirconium relative to the total number of moles of cerium (Ce) and zirconium (Zr) (X=Zr / (Ce+Zr)×100) must be 44.5-49.9%, and is preferably 47.0-49.9%. If the molar fraction of zirconium is below the lower limit, it becomes difficult to obtain a sufficient oxygen storage capacity (OSC), while if it exceeds the upper limit, it becomes difficult to obtain a single phase.

[0034] In addition, the oxygen storage material of the present invention has a lattice constant determined from X-ray diffraction patterns obtained by X-ray diffraction measurement using CuKα before heating at 1100° C. in air (before the high-temperature durability test) and after heating for 5 hours (after the high-temperature durability test) that satisfies the following formula (1): Lattice constant ≦-9.69×10 -3 X+11.009 (1) (In the above formula, X represents the mole fraction of zirconium.) The condition expressed by The intensity ratio [I(14 / 29) value] of the diffraction line near 2θ=14.5° and the diffraction line near 2θ=29° obtained from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα before and after the high-temperature durability test is expressed by the following formula (2): I(14 / 29) value ≦ 5.15 × 10 -3 X-0.196 (2) (In the above formula, X represents the mole fraction of zirconium.) In an oxygen storage material in which the lattice constant before and after the high-temperature durability test satisfies the condition represented by formula (1) and the I(14 / 29) value before and after the high-temperature durability test satisfies the condition represented by formula (2), the added metal element is sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide, and the material can exhibit excellent oxygen storage capacity (OSC) at a low temperature of about 250°C not only in the initial stage of use but also after long-term exposure to high-temperature exhaust gases at about 1100°C, thereby demonstrating high utilization efficiency. On the other hand, if the lattice constants before and after the high-temperature durability test do not satisfy the condition represented by formula (1), or if the I(14 / 29) values ​​before and after the high-temperature durability test do not satisfy the condition represented by formula (2), the added metal element is not sufficiently dissolved in the pyrochlore-type ceria-zirconia composite oxide, and therefore the oxygen storage capacity (OSC) at a low temperature of about 250°C is not fully exhibited either at the beginning of use or after long-term exposure to high-temperature exhaust gas at about 1100°C, and the utilization efficiency as an oxygen storage material is also low.

[0035] Here, the diffraction line near 2θ=14.5° is a diffraction line assigned to the (111) plane of the ordered phase, and the diffraction line near 2θ=29° is a diffraction line assigned to the (222) plane of the ordered phase overlapping with a diffraction line assigned to the (111) plane of the cubic phase of the ceria-zirconia solid solution (CZ solid solution). Therefore, by calculating the I(14 / 29) value, which is the intensity ratio of the two diffraction lines, it is defined as an index showing the maintenance rate (abundance rate) of the superlattice structure (ordered phase).

[0036] Furthermore, the average crystallite diameter of the oxygen storage material of the present invention is preferably 0.1 to 10 μm, more preferably 0.2 to 5 μm. If the average crystallite diameter is less than the lower limit, the I(14 / 29) value indicating the maintenance rate of the superlattice structure after the high-temperature durability test tends to be easily reduced, while if it exceeds the upper limit, the effect of improving the oxygen storage capacity (OSC) tends to be difficult to obtain sufficiently. The average crystallite diameter can be calculated based on the Scherrer formula using a commercially available analysis software (for example, "JADE" manufactured by Materials Data Corporation) using the half-width of the diffraction line near 2θ=29° obtained from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα.

[0037] The specific surface area of ​​the oxygen storage material of the present invention is not particularly limited, but is preferably 0.01 to 20 m 2 / g, and 0.05 to 10 m 2 / g is more preferable, and 0.1 to 5m 2 / g is even more preferable. If the specific surface area is less than the lower limit, the oxygen storage capacity tends to be small, while if it exceeds the upper limit, the number of particles with small particle diameters increases, and the heat resistance tends to decrease. The specific surface area can be calculated as the BET specific surface area from the adsorption isotherm using the BET isothermal adsorption equation.

[0038] In addition, the oxygen storage material of the present invention may further contain at least one element selected from the group consisting of rare earth elements other than cerium and scandium and alkaline earth elements other than magnesium. By containing such an element, when the oxygen storage material of the present invention is used as a carrier for an exhaust gas purification catalyst, a higher exhaust gas purification ability tends to be exhibited. Such rare earth elements other than cerium and scandium include yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), ytterbium (Yb), lutetium (Lu), etc., among which, from the viewpoint of tending to stabilize the superlattice structure, La, Nd, Pr, Y are preferred, and La, Y, Nd are more preferred. In addition, examples of alkaline earth metal elements other than magnesium include calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra). Among these, Ca and Ba are preferred from the viewpoint of their tendency to stabilize the superlattice structure.

[0039] Furthermore, when at least one element selected from the group consisting of rare earth elements other than cerium and scandium and alkaline earth elements other than magnesium is further contained, the content of the element is preferably 0.5 to 20 at%, more preferably 1 to 10 at%, based on the total amount of cerium (Ce) and zirconium (Zr). If the content of such an element is less than the lower limit, the effect of stabilizing the superlattice structure tends to decrease, while if it exceeds the upper limit, the oxygen storage capacity tends to decrease.

[0040] The oxygen storage material of the present invention contains the pyrochlore-type ceria-zirconia composite oxide and the additive metal element added to the ceria-zirconia composite oxide, and can exhibit excellent oxygen storage capacity (OSC) at a low temperature of about 250°C, not only at the beginning of use but also after long-term exposure to high-temperature exhaust gas of about 1100°C. Therefore, the oxygen storage material of the present invention is suitably used as a support or co-catalyst for exhaust gas purification catalysts. A suitable example of using such an oxygen storage material of the present invention is an exhaust gas purification catalyst consisting of a support made of the oxygen storage material of the present invention and a precious metal supported on the support. Examples of such precious metals include platinum, rhodium, palladium, osmium, iridium, gold, silver, etc. Another example is one in which the oxygen storage material of the present invention is arranged around an exhaust gas purification catalyst in which a precious metal is supported on other catalyst support fine particles.

[0041] Next, a method for producing the oxygen storage material of the present invention will be described. The method for producing the oxygen storage material of the present invention is a method for producing an oxygen storage material containing a pyrochlore-type ceria-zirconia composite oxide and at least one additive metal element selected from the group consisting of tin, scandium, and magnesium added to the ceria-zirconia composite oxide, A step (first step) of preparing a ceria-zirconia solid solution powder containing the additive metal element (M), in which the content ratio (M / (Ce+Zr)×100) of the additive metal element (M) relative to the total amount of cerium (Ce) and zirconium (Zr) is 0.4-5.5 at% and the molar fraction (Zr / (Ce+Zr)×100) of zirconium relative to the total number of moles of cerium (Ce) and zirconium (Zr) is 44.5-49.9%; a step (second step) of compressing the ceria-zirconia solid solution powder containing the additive metal element at a pressure of 30 to 350 MPa, reducing the powder at a temperature of 1400 to 2000°C, and then oxidizing the powder to obtain an oxygen storage material containing the pyrochlore-type ceria-zirconia composite oxide according to claim 1 or 2 and the additive metal element added to the ceria-zirconia composite oxide; The method includes:

[0042] First, in a first step, a ceria-zirconia solid solution powder containing an additive metal element is prepared, the additive metal element containing ceria-zirconia solid solution powder containing at least one additive metal element selected from the group consisting of tin (Sn), scandium (Sc) and magnesium (Mg), the content ratio of the additive metal element (M) to the total amount of cerium (Ce) and zirconium (Zr) (M / (Ce+Zr)×100) is 0.4 to 5.5 at% (preferably, 1 to 3 at%), and the molar fraction of zirconium to the total number of moles of cerium (Ce) and zirconium (Zr) (Zr / (Ce+Zr)×100) is 44.5 to 49.9% (preferably, 47.0 to 49.9%).

[0043] In the ceria-zirconia solid solution powder containing the additive metal element, if the content of the additive metal element is less than the lower limit, the effect of improving the oxygen storage capacity (OSC) at low temperatures and the effect of improving the utilization efficiency as an oxygen storage material due to the solid solution of the additive metal element in the obtained oxygen storage material are difficult to be sufficiently obtained, while if the content exceeds the upper limit, the additive metal element is not sufficiently solid-dissolved in the obtained oxygen storage material, and the effect of improving the oxygen storage capacity (OSC) at low temperatures and the effect of improving the utilization efficiency as an oxygen storage material are difficult to be sufficiently obtained. Also, if the mole fraction of the zirconium is less than the lower limit, the oxygen storage material is difficult to obtain a sufficient oxygen storage capacity (OSC), while if the mole fraction exceeds the upper limit, it is difficult to obtain an oxygen storage material as a single phase.

[0044] In addition, in the case of the ceria-zirconia solid solution powder containing the additive metal element, it is preferable to use a solid solution in which ceria and zirconia are mixed at the atomic level, from the viewpoint of more fully forming a superlattice structure. Furthermore, such a ceria-zirconia solid solution powder containing the additive metal element has an average primary particle size of preferably about 2 to 100 nm, more preferably about 5 to 70 nm, and a specific surface area of ​​1.0 to 100 m. 2 / g, and 10 to 80m 2 / g is more preferable, and 30 to 80m2 It is even more preferred that the .mu.m / g.

[0045] The method for preparing (preparing) such a ceria-zirconia solid solution powder containing an additive metal element is not particularly limited, and examples thereof include a method of producing the solid solution powder by adopting a so-called coprecipitation method so that the content ratio of cerium, zirconium, and the additive metal element falls within the above range. Examples of such a coprecipitation method include a method in which an aqueous solution containing a cerium salt (e.g., a nitrate salt), a zirconium salt (e.g., a nitrate salt), and the additive metal salt (e.g., a nitrate salt) is used to generate a coprecipitate in the presence of ammonia, and the obtained coprecipitate is centrifuged, washed, dried, and further calcined, and then pulverized using a pulverizer such as a ball mill to obtain the additive metal element-containing ceria-zirconia solid solution powder. The aqueous solution containing the cerium salt, the zirconium salt, and the additive metal salt is prepared so that the content ratio of cerium, zirconium, and the additive metal element in the obtained solid solution powder falls within a predetermined range. Furthermore, such an aqueous solution may contain, as necessary, a salt of at least one element selected from the group consisting of rare earth elements and alkaline earth elements, a surfactant (for example, a nonionic surfactant), and the like.

[0046] In addition, the ceria-zirconia solid solution powder containing the additive metal element may further contain at least one element selected from the group consisting of rare earth elements other than cerium and scandium and alkaline earth elements other than magnesium. By containing such an element, when the oxygen storage material of the present invention is used as a co-catalyst for an exhaust gas purification catalyst, a higher exhaust gas purification ability tends to be exhibited. Examples of such rare earth elements other than cerium and scandium include yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), ytterbium (Yb), and lutetium (Lu). Among them, La, Nd, Pr, and Y are preferred, and La, Y, and Nd are more preferred, from the viewpoint of tending to stabilize the superlattice structure. In addition, examples of alkaline earth metal elements other than magnesium include calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra). Among these, Ca and Ba are preferred from the viewpoint of their tendency to stabilize the superlattice structure.

[0047] Furthermore, when at least one element selected from the group consisting of rare earth elements other than cerium and scandium and alkaline earth elements other than magnesium is further contained, the content of the element is preferably 0.5 to 20 at%, more preferably 1 to 10 at%, based on the total amount of cerium (Ce) and zirconium (Zr) in the ceria-zirconia solid solution powder containing the additive metal element. If the content of such an element is less than the lower limit, it tends to be difficult to stabilize the superlattice structure, while if it exceeds the upper limit, the oxygen storage capacity tends to decrease.

[0048] Next, in the second step, the ceria-zirconia solid solution powder containing the additive metal element is pressure-molded at a pressure of 30 to 350 MPa (preferably, a pressure of 40 to 300 MPa). If the pressure molding pressure is less than the lower limit, the contact between the secondary particles of the powder is not improved, so that the crystal growth during the reduction treatment is not sufficiently promoted, and the stability of the superlattice structure when exposed to high-temperature exhaust gas of about 1100°C for a long period of time is reduced. On the other hand, if the pressure molding pressure exceeds the upper limit, the crystal growth during the reduction treatment progresses too much, and the oxygen storage capacity (OSC) at a low temperature of about 300°C tends to decrease. The method of such pressure molding is not particularly limited, and a known pressure molding method such as a hydrostatic press can be appropriately adopted.

[0049] Next, in the second step, the pressure-molded solid solution powder compact is subjected to a reduction treatment in which the compact is heated under reducing conditions at a temperature of 1400 to 2000°C (preferably 1600 to 1900°C) for 0.5 to 24 hours (preferably 1 to 10 hours), and then subjected to an oxidation treatment to obtain the oxygen storage material powder of the present invention. If the temperature of the reduction treatment is below the lower limit, crystal growth does not proceed sufficiently, and the stability of the superlattice structure decreases. On the other hand, if the temperature of the reduction treatment exceeds the upper limit, the balance between the energy (e.g., power) required for the reduction treatment and the improvement of performance becomes poor. In addition, if the heating time during the reduction treatment is below the lower limit, the superlattice structure tends to be difficult to form sufficiently, and on the other hand, if the heating time exceeds the upper limit, the balance between the energy (e.g., power) required for the reduction treatment and the improvement of performance becomes poor.

[0050] The method of the reduction treatment is not particularly limited as long as it is a method that can heat-treat the solid solution powder under a reducing atmosphere under a predetermined temperature condition, and examples thereof include (i) a method in which the solid solution powder is placed in a vacuum heating furnace, evacuated, and then a reducing gas is introduced into the furnace to create a reducing atmosphere in the furnace and heated under a predetermined temperature condition to perform the reduction treatment; (ii) a method in which the solid solution powder is placed in a graphite furnace, evacuated, and then heated under a predetermined temperature condition to create a reducing atmosphere in the furnace by reducing gases such as CO and HC generated from the furnace body, heating fuel, etc., to perform the reduction treatment; and (iii) a method in which the solid solution powder is placed in a crucible filled with activated carbon, and then heated under a predetermined temperature condition to create a reducing atmosphere in the crucible by reducing gases such as CO and HC generated from the activated carbon, etc., to perform the reduction treatment.

[0051] The reducing gas used to achieve such a reducing atmosphere is not particularly limited, and reducing gases such as CO, HC, H2, and other hydrocarbon gases can be appropriately used. Among such reducing gases, it is more preferable to use one that does not contain carbon (C) from the viewpoint of preventing the generation of by-products such as zirconium carbide (ZrC) when performing reduction treatment at a higher temperature. When such a reducing gas that does not contain carbon (C) is used, reduction treatment can be performed at a higher temperature condition close to the melting point of zirconium, etc., and the structural stability of the crystal phase can be sufficiently improved.

[0052] Furthermore, in the second step, an oxidation treatment is further carried out after the reduction treatment. By carrying out such an oxidation treatment, oxygen lost during reduction is compensated for in the obtained ceria-zirconia composite oxide containing the additive metal element, and the stability as an oxide is improved. The method of such an oxidation treatment is not particularly limited, and for example, a method of heat treating the ceria-zirconia composite oxide containing the additive metal element in an oxidizing atmosphere (for example, in air) can be suitably adopted. In addition, the heating temperature condition in such an oxidation treatment is not particularly limited, but is preferably about 300 to 800°C. Furthermore, the heating time in the oxidation treatment is not particularly limited, but is preferably about 0.5 to 5 hours.

[0053] In the second step, it is preferable to further subject the ceria-zirconia-based composite oxide containing the added metal element to a pulverization treatment after the reduction treatment and / or the oxidation treatment. The method of such a pulverization treatment is not particularly limited, and for example, a wet pulverization method, a dry pulverization method, a freeze pulverization method, etc. can be suitably adopted. EXAMPLES

[0054] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0055] Example 1 First, 245.7g of cerium nitrate aqueous solution with a concentration of 28% by mass in terms of CeO2, 270.6g of zirconium nitrate aqueous solution with a concentration of 18% by mass in terms of ZrO2, and an aqueous solution in which 1.4g of tin chloride pentahydrate was dissolved in 100ml of pure water were mixed, and the resulting mixed solution was added to a solution in which 163.2g of 25% ammonia water was diluted with 400ml of pure water, and the mixture was stirred at 1000 rpm for 10 minutes using a homogenizer (manufactured by AS ONE Corporation) to generate a coprecipitate. The resulting coprecipitate was dried in the air at 150°C for 7 hours using a degreasing furnace, and then calcined in the air at 400°C for 5 hours to obtain a tin-containing ceria-zirconia solid solution. The solid solution was then pulverized using a pulverizer ("Wonder Blender" manufactured by AS ONE Corporation) so that the particle size was 75 μm or less by sieving, and a tin-containing ceria-zirconia solid solution powder was obtained in which the atomic ratio of cerium, zirconium, and tin ([Ce]:[Zr]:[Sn]) was 50:49.5:0.5. In this tin-containing ceria-zirconia solid solution powder, the tin content ratio (Sn / (Ce+Zr)×100) to the total amount of cerium and zirconium was 0.5 at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (Zr / (Ce+Zr)×100) was 49.7%.

[0056] Next, 20 g of this tin-containing ceria-zirconia solid solution powder was packed into a polyethylene bag (volume 0.05 L), and after the inside was degassed, the mouth of the bag was heated and sealed. Then, a hydrostatic press ("CK4-22-60" manufactured by Nikkiso Co., Ltd.) was used to apply 3000 kgf / cm to the bag. 2 The powder was subjected to cold isostatic pressing (CIP) at a pressure (molding pressure) of 294 MPa for 1 minute to obtain a molded body of the tin-containing ceria-zirconia solid solution powder. The size of the molded body was 20 mm in length, 20 mm in width, 3 mm in average thickness, and approximately 10 g in mass.

[0057] The obtained molded body was then placed in a small vacuum pressure sintering furnace (FVPS-R-150 manufactured by Fuji Denpa Kogyo Co., Ltd.) and replaced with an argon atmosphere. Thereafter, the furnace was heated to 1000°C over a heating time of 1 hour, then heated to 1700°C (reduction treatment temperature) over a heating time of 4 hours and held at that temperature for 5 hours. After that, the furnace was cooled to 1000°C over a cooling time of 4 hours, and then allowed to cool naturally to room temperature to obtain a reduction-treated product.

[0058] The obtained reduction treatment product was heated in air at 500°C for 5 hours to obtain a tin-containing ceria-zirconia composite oxide. This tin-containing ceria-zirconia composite oxide was pulverized using the pulverizer so that the particle size was 75μm or less to obtain a tin-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Sn]) of 50:49.5:0.5 of cerium, zirconium, and tin. In this tin-containing ceria-zirconia composite oxide powder, the content ratio of tin to the total amount of cerium and zirconium (Sn / (Ce+Zr)×100) was 0.5at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100) was X=49.7%.

[0059] Example 2 A scandium-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Sc]) of cerium, zirconium, and scandium was obtained in the same manner as in Example 1, except that the amount of the zirconium nitrate aqueous solution was changed to 267.9 g and 2.4 g of scandium nitrate tetrahydrate was used instead of the tin chloride pentahydrate. In this scandium-containing ceria-zirconia composite oxide powder, the content ratio of scandium to the total amount of cerium and zirconium (Sc / (Ce+Zr)×100) was 1.0 at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100) was X=49.5%.

[0060] Example 3 A scandium-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Sc]) of 50:47.5:2.5 of cerium, zirconium, and scandium was obtained in the same manner as in Example 2, except that the amount of the zirconium nitrate aqueous solution was changed to 259.7 g and the amount of the scandium nitrate tetrahydrate was changed to 6.1 g. In this scandium-containing ceria-zirconia composite oxide powder, the content ratio of scandium to the total amount of cerium and zirconium (Sc / (Ce+Zr)×100) was 2.6 at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100) was X=48.7%.

[0061] Example 4 First, 258.6g of cerium nitrate aqueous solution with a concentration of 28% by mass in terms of CeO2 and 258.9g of zirconium nitrate aqueous solution with a concentration of 18% by mass in terms of ZrO2 were mixed, and the resulting mixed solution was added to a solution obtained by diluting 164.9g of 25% ammonia water with 500ml of pure water, and the mixture was stirred at 1000 rpm for 10 minutes using a homogenizer (manufactured by AS ONE Corporation) to generate a coprecipitate. The resulting coprecipitate was dried in air at 150°C for 7 hours using a degreasing furnace, and then calcined in air at 400°C for 5 hours to obtain a ceria-zirconia solid solution powder. 1.1g of scandium nitrate tetrahydrate was added to 9.8g of this solid solution powder so that the amount was 0.2g in terms of Sc2O3, and the mixture was evaporated to dryness at 110°C for 12 hours. The resulting dried product was fired in air at 700°C for 5 hours, and then pulverized using a pulverizer (Azwan Corporation's "Wonder Blender") to a particle size of 75μm or less by sieving, to obtain a scandium-containing ceria-zirconia solid solution powder with an atomic ratio ([Ce]:[Zr]:[Sc]) of 50:45:5 of cerium, zirconium, and scandium. In this scandium-containing ceria-zirconia solid solution powder, the content ratio of scandium to the total amount of cerium and zirconium (Sc / (Ce+Zr)×100) is 5.3at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (Zr / (Ce+Zr)×100) is 47.4%.

[0062] Next, a scandium-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Sc]) of cerium, zirconium, and scandium was obtained in the same manner as in Example 1, except that 10 g of the scandium-containing ceria-zirconia solid solution powder was used instead of the tin-containing ceria-zirconia solid solution powder. In this scandium-containing ceria-zirconia composite oxide powder, the content ratio of scandium to the total amount of cerium and zirconium (Sc / (Ce+Zr)×100) was 5.3 at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100) was X=47.4%.

[0063] Example 5 A magnesium-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Mg]) of 50:47.5:2.5 of cerium, zirconium, and magnesium was obtained in the same manner as in Example 3, except that 5.1 g of magnesium nitrate hexahydrate was used instead of scandium nitrate tetrahydrate. In this magnesium-containing ceria-zirconia composite oxide powder, the magnesium content ratio (Mg / (Ce+Zr)×100) to the total amount of cerium and zirconium was 2.6 at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100) was X=48.7%.

[0064] Example 6 A magnesium-containing ceria-zirconia composite oxide powder having an atomic ratio ([Ce]:[Zr]:[Mg]) of 50:45:5 of cerium, zirconium, and magnesium was obtained in the same manner as in Example 4, except that 0.9 g of magnesium nitrate hexahydrate was used instead of scandium nitrate tetrahydrate. In this magnesium-containing ceria-zirconia composite oxide powder, the magnesium content ratio (Mg / (Ce+Zr)×100) to the total amount of cerium and zirconium was 5.3 at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100) was X=47.4%.

[0065] Comparative Example 1 A ceria-zirconia composite oxide powder having a content ratio of cerium, zirconium, and added metal element M of 50:50:0 in atomic ratio ([Ce]:[Zr]:[M]) was obtained in the same manner as in Example 1, except that the amount of the zirconium nitrate aqueous solution was changed to 273.4 g and the tin chloride pentahydrate was not added. In this ceria-zirconia composite oxide powder, the content ratio of added metal element M to the total amount of cerium and zirconium (M / (Ce+Zr)×100) was 0 at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100) was X=50%.

[0066] Comparative Example 2 A titanium-containing ceria-zirconia composite oxide powder having a cerium, zirconium, and titanium content ratio of 50:40:10 in atomic ratio ([Ce]:[Zr]:[Ti]) was obtained in the same manner as in Example 1, except that the amount of the zirconium nitrate aqueous solution was changed to 218.7 g, and 15.0 g (Ti content: 0.08 mole) of titanium oxynitrate aqueous solution was used instead of the tin chloride pentahydrate. In this titanium-containing ceria-zirconia composite oxide powder, the titanium content ratio (Ti / (Ce+Zr)×100) to the total amount of cerium and zirconium was 11.1 at%, and the molar fraction of zirconium to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100) was X=44.4%.

[0067] (Comparative Example 3) A ceria-zirconia solid solution powder was obtained in the same manner as in Example 4, except that the amount of the cerium nitrate aqueous solution was changed to 273.0 g, the amount of the zirconium nitrate aqueous solution was changed to 243.0 g, and the amount of the 25% aqueous ammonia was changed to 166.8 g. To 9.8 g of this solid solution powder, 2.1 g of scandium nitrate tetrahydrate was added so as to be 0.5 g in terms of Sc2O3, and in the same manner as in Example 4, a scandium-containing ceria-zirconia composite oxide powder having a content ratio of cerium, zirconium, and scandium of 50:40:10 in atomic ratio ([Ce]:[Zr]:[Sc]) was obtained. In this scandium-containing ceria-zirconia composite oxide powder, the content ratio of scandium to the total amount of cerium and zirconium (Sc / (Ce+Zr)×100) is 11.1 at%, and the mole fraction of zirconium to the total number of moles of cerium and zirconium (Zr / (Ce+Zr)×100) is X = 44.4%.

[0068] (Comparative Example 4) A magnesium-containing ceria-zirconia composite oxide powder having a content ratio of cerium, zirconium, and magnesium of 50:40:10 in atomic ratio ([Ce]:[Zr]:[Mg]) was obtained in the same manner as in Comparative Example 3, except that 1.8 g of magnesium nitrate hexahydrate was added instead of scandium nitrate tetrahydrate. In this magnesium-containing ceria-zirconia composite oxide powder, the content ratio of magnesium to the total amount of cerium and zirconium (Mg / (Ce+Zr)×100) is 11.1 at%, and the mole fraction of zirconium to the total number of moles of cerium and zirconium (X = Zr / (Ce+Zr)×100) is X = 44.4%.

[0069] <High-temperature durability test> The composite oxide powders obtained in the examples and comparative examples were heated in air at 1100°C for 5 hours.

[0070] <X-ray diffraction (XRD) measurement> The X-ray diffraction patterns of each composite oxide powder obtained in the Examples and Comparative Examples before and after the high-temperature durability test were measured using an X-ray diffractometer (Rigaku Corporation, "RINT-Ultima") under conditions of a tube voltage of 40 KV, a tube current of 40 mA, and a scanning speed of 2θ = 10° / min, using CuKα radiation as the X-ray source.

[0071] The obtained X-ray diffraction pattern was fitted by the least squares method using the Rietveld analysis software "Jana2006" to refine the lattice constants. The obtained lattice constants are shown in Table 1.

[0072] In the obtained X-ray diffraction pattern, the ratio of the peak intensity I(14) of the diffraction line near 2θ=14.5° to the peak intensity I(29) of the diffraction line near 2θ=29° [I(14 / 29)=I(14) / I(29)] was calculated. The results are shown in Table 1.

[0073] <Catalyst preparation> Each of the composite oxide powders obtained in the Examples and Comparative Examples after the high-temperature durability test was impregnated with a dinitrodiammineplatinum(II) acid solution, evaporated to dryness, and then calcined at 300°C for 3 hours to prepare a catalyst powder in which platinum (Pt) was supported on the composite oxide powder containing the added metal element (Pt loading: 1% by mass).

[0074] <Oxygen release measurement> 15 mg of each catalyst powder prepared as described above was placed in a thermogravimetric analyzer (Shimadzu Corporation, "TGA-50"), and a rich gas (H2 (5% by volume) + N2 (balance)) at a temperature of 250 and a lean gas (O2 (5% by volume) + N2 (balance)) were alternately passed through the catalyst powder at a gas flow rate of 100 ml / min every 5 minutes, and the increase or decrease in the mass of the catalyst powder during this period was measured. The average mass loss of the catalyst powder during the second and third rich gas passes was calculated, and this was taken as the oxygen release amount (measured value). The ratio of the oxygen release amount (measured value) to the maximum oxygen release amount (theoretical value) based on the amount of cerium in the catalyst powder was calculated, and this was taken as the oxygen storage material (OSC material) utilization rate. The results are shown in Table 1.

[0075] [Table 1]

[0076] From the I(14 / 29) values ​​shown in Table 1, it was confirmed that the oxygen storage materials obtained in Examples 1 to 6 and Comparative Examples 1 to 4 contained a pyrochlore-type ceria-zirconia composite oxide.

[0077] Based on the results shown in Table 1, the lattice constant and I(14 / 29) value were plotted against the zirconium mole fraction X. These results are shown in Figures 1 and 2. The straight line in Figure 1 corresponds to the following formula (1a): Lattice constant (Y1) = -9.69 x 10 -3 X+11.009 (1a) The figure shows the relationship between the lattice constant (Y1) of the oxygen storage material powder, which is represented by the formula (2a): and the mole fraction of zirconium relative to the total number of moles of cerium and zirconium (X=Zr / (Ce+Zr)×100). The straight line in FIG. 2 is expressed by the formula (2a): I(14 / 29) value(Y2)=5.15×10 -3 X-0.196 (2a) 1 shows the relationship between the I(14 / 29) value (Y2) of the oxygen storage material powder, expressed as: and the mole fraction of zirconium relative to the total mole number of cerium and zirconium (X=Zr / (Ce+Zr)×100).

[0078] Furthermore, for each composite oxide powder after the high-temperature durability test, the OSC material utilization rate of the catalyst powder was plotted against the zirconium mole fraction X. These results are shown in FIG.

[0079] As shown in FIGS. 1 and 2, the additive metal element-containing ceria-zirconia solid solution powder in which the content ratio (M / (Ce+Zr)×100) of the additive metal element (M=Sn, Sc, or Mg) and the molar fraction (Zr / (Ce+Zr)×100) of zirconium are within a predetermined range are pressure-molded, the resulting molded body is reduced, and then oxidized to obtain the additive metal element-containing ceria-zirconia composite oxide powders (Examples 1 to 6). Both before and after the high-temperature durability test, the lattice constants of the additive metal element-containing ceria-zirconia composite oxide powders satisfy the condition represented by formula (1) and the I(14 / 29) values ​​satisfy the condition represented by formula (2). This indicates that the additive metal atoms are sufficiently dissolved in the lattice of the pyrochlore-type ceria-zirconia composite oxide.

[0080] In addition, the pyrochlore-type ceria-zirconia composite oxide that does not contain the above-mentioned additive metal element is usually added with Zr 4+ Sc has a larger ionic radius than 3+ When Ce is dissolved in the solid solution, the difference in ionic radius between the Ce site and the Zr site becomes smaller, and therefore the I(14 / 29) value becomes smaller. However, in Example 3, the I(14 / 29) value before the high-temperature durability test was larger than that of Comparative Example 1. The reason for this is not entirely clear, but the present inventors speculate as follows. That is, in Example 3, it is considered possible that a portion of Ce was reduced. This reduction resulted in the formation of Ce. 4+ (Ionic radius: 0.97 Å) is Ce 3+ (ionic radius: 1.14 Å), there are areas where the ionic radius difference between the Ce site and the Zr site is large, and this increase in the ionic radius difference increases the I(14 / 29) value. 3+ It is considered that the effect of the solid solution of ZnO, which reduces the I(14 / 29) value, competed with the effect of the solid solution of ZnO, which reduces the I(14 / 29) value. As a result, the I(14 / 29) value before the high-temperature durability test was smaller than the value calculated by the above formula (2a) and larger than that of Comparative Example 1.

[0081] On the other hand, the titanium-containing ceria-zirconia composite oxide powder (Comparative Example 2) obtained by pressure molding the titanium-containing ceria-zirconia solid solution powder, reducing the obtained molded body, and further oxidizing it had a lattice constant that satisfied the condition represented by the above formula (1) both before and after the high-temperature durability test, but the I(14 / 29) value before the high-temperature durability test did not satisfy the condition represented by the above formula (2). This is because Ti 4+ The ionic radius of Zr 4+ This is believed to be because the ionic radius difference between the Ce site and the Zr site is large, and the I(14 / 29) value after the high-temperature durability test in the titanium-containing ceria-zirconia composite oxide powder obtained in Comparative Example 2 was smaller than the I(14 / 29) value calculated by the above formula (2a). This is not because titanium atoms were dissolved in the pyrochlore-type ceria-zirconia composite oxide by the high-temperature durability test, but because the phase separation of ceria was promoted by the titanium atoms that were not dissolved, decreasing the stability of the pyrochlore-type ceria-zirconia composite oxide.

[0082] In addition, the additive metal element-containing ceria-zirconia composite oxide powder (Comparative Examples 3 and 4) obtained by pressure molding the additive metal element-containing ceria-zirconia solid solution powder in which the content ratio of the additive metal element M (M / (Ce+Zr)×100) is greater than a predetermined range, reducing the obtained molded body, and further oxidizing the molded body had a lattice constant that satisfied the condition represented by the formula (1) both before and after the high-temperature durability test, but the I(14 / 29) value before the high-temperature durability test did not satisfy the condition represented by the formula (2), so it is considered that the additive metal atoms are not sufficiently dissolved in the lattice of the pyrochlore-type ceria-zirconia composite oxide. In the additive metal element-containing ceria-zirconia composite oxide powder obtained in Comparative Examples 3 and 4, the increase rate of the lattice constant relative to the increase in the amount of the additive metal element was smaller than in Examples 2 to 4 and Examples 5 to 6. This is considered to be due to the phase separation of ceria from the ceria-zirconia composite oxide powder by the additive metal atoms that are not dissolved. In the case of the ceria-zirconia composite oxide powders containing the added metal elements obtained in Comparative Examples 3 and 4, the I(14 / 29) value after the high-temperature durability test was smaller than the I(14 / 29) value calculated by the formula (2a). This is not because the added metal atoms were dissolved in the pyrochlore-type ceria-zirconia composite oxide by the high-temperature durability test, but is believed to be because the added metal atoms that were not dissolved promoted phase separation of ceria, thereby reducing the stability of the pyrochlore-type ceria-zirconia composite oxide.

[0083] As shown in FIG. 3, after the high-temperature durability test, the catalyst powder containing the oxygen storage material powder made of a composite oxide powder in which the added metal atoms (Sn, Sc, or Mg) are sufficiently dissolved in the lattice of the pyrochlore-type ceria-zirconia composite oxide (i.e., the oxygen storage material powder satisfying both of the conditions represented by the formulas (1) and (2)) was superior to the catalyst powder containing the oxygen storage material powder made of a pyrochlore-type ceria-zirconia composite oxide not containing the added metal atoms (Comparative Example 1), Zr 4+It was found that the utilization rate of the oxygen storage material (OSC material) is higher than that of a catalyst powder (Comparative Example 2) containing an oxygen storage material powder made of a complex oxide powder in which titanium atoms, which have an extremely small ionic radius compared to titanium atoms, are dissolved in the lattice of a pyrochlore-type ceria-zirconia complex oxide, and the phase separation of ceria is promoted by the titanium atoms that are not dissolved, reducing the stability of the pyrochlore-type ceria-zirconia complex oxide, and than that of a catalyst powder (Comparative Examples 3 and 4) containing an oxygen storage material powder made of a complex oxide powder in which the added metal atoms are not sufficiently dissolved in the lattice of the pyrochlore-type ceria-zirconia complex oxide (i.e., an oxygen storage material powder that does not satisfy the condition represented by formula (2) before the high-temperature durability test). [Industrial Applicability]

[0084] As explained above, it is possible to obtain an oxygen storage material with high utilization efficiency that can exhibit excellent oxygen storage capacity (OSC) at a low temperature of about 250°C not only at the beginning of use but also after long-term exposure to high-temperature exhaust gas at about 1100°C. Therefore, since the oxygen storage material of the present invention has both excellent oxygen storage capacity (OSC) at low temperatures and high-temperature durability, it is useful as a support or co-catalyst for exhaust gas purification catalysts, a catalyst atmosphere adjuster, etc.

Claims

1. An oxygen storage material containing a pyrochlore-type ceria-zirconia composite oxide and at least one additive metal element selected from the group consisting of tin and scandium added to the ceria-zirconia composite oxide, The content ratio (M / (Ce+Zr)×100) of the added metal element (M) relative to the total amount of cerium (Ce) and zirconium (Zr) is 0.4 to 5.5 at %, The mole fraction of zirconium relative to the total mole number of cerium (Ce) and zirconium (Zr) (X=Zr / (Ce+Zr)×100) is X=44.5% to 49.9%; Before and after heating at 1100° C. in air for 5 hours, the lattice constant calculated from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα is expressed by the following formula (1): Lattice constant ≦-9.69×10-3X+11.009 (1) (wherein X represents the mole fraction of zirconium) The condition expressed by The intensity ratio [I(14 / 29) value] of the diffraction line near 2θ=14.5° to the diffraction line near 2θ=29° obtained from the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα before and after heating at 1100° C. in air is expressed by the following formula (2): I(14 / 29) value≦5.15×10−3X−0.196 (2) (wherein X represents the mole fraction of zirconium) The oxygen storage material is characterized in that it satisfies the conditions represented by the formula:

2. 2. The oxygen storage material according to claim 1, wherein the zirconium mole fraction X is 47.0 to 49.9%.

3. A method for producing an oxygen storage material containing a pyrochlore-type ceria-zirconia composite oxide and at least one additive metal element selected from the group consisting of tin, scandium, and magnesium added to the ceria-zirconia composite oxide, comprising: A step of preparing a ceria-zirconia solid solution powder containing the additive metal element (M), in which the content ratio (M / (Ce+Zr)×100) of the additive metal element (M) relative to the total amount of cerium (Ce) and zirconium (Zr) is 0.4 to 5.5 at %, and the molar fraction (Zr / (Ce+Zr)×100) of zirconium relative to the total number of moles of cerium (Ce) and zirconium (Zr) is 44.5 to 49.9%; a step of compressing and molding the ceria-zirconia solid solution powder containing the additive metal element at a pressure of 30 to 350 MPa, reducing the powder at a temperature of 1400 to 2000° C., and then oxidizing the powder to obtain an oxygen storage material containing the pyrochlore-type ceria-zirconia composite oxide according to claim 1 or 2 and the additive metal element added to the ceria-zirconia composite oxide; A method for producing an oxygen storage material, comprising:

4. 4. The method for producing an oxygen storage material according to claim 3, wherein the molar fraction of zirconium in the ceria-zirconia solid solution powder containing the additive metal element (Zr / (Ce+Zr)×100) is 47.0 to 49.9%.

Citation Information

Patent Citations

  • Oxygen absorbing / releasing material and exhaust gas purification catalyst containing the same

    JP2015080736A

  • Cerium-zirconium type complex oxide and production method thereof

    JP2015182931A

  • Cerium-zirconium type complex oxide and production method thereof

    JP2015182932A

  • Oxygen storage material and manufacturing method therefor

    JP2019131455A

  • Oxygen storage material and method for producing the same

    JP2020059630A